2014
DOI: 10.1002/cmmi.1633
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall particles for Gd‐MRI and 68Ga‐PET dual imaging

Abstract: Nanoparticles made of a polysiloxane matrix and surrounded by 1,4,7,10-tetraazacyclododecane-1-glutaric anhydride-4,7,10-triacetic acid (DOTAGA)[Gd(3+) ] and 2,2'-(7-(1-carboxy-4-((2,5-dioxopyrrolidin-1-yl)oxy)-4-oxobutyl)-1,4,7-triazonane-1,4-diyl)diacetic acid) NODAGA[(68) Ga(3+) ] have been synthesized for positron emission tomography/magnetic resonance (PET/MRI) dual imaging. Characterizations were carried out in order to determine the nature of the ligands available for radiolabelling and to quantify them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Apart from the kidneys and blood, no major uptake in all analyzed tissues is noted (<1.5% ID/g from 30 min p.i.). These results are in accordance to ex vivo biodistribution studies previously performed in normal Swiss mice, which showed that 68 GaAGuIX@NODAGA cleared rapidly from the blood via the kidneys to the urine, resulting in extremely low background activity in all other tissues [17]. While the actual tumor uptake dropped from 30 to 120 min p.i., the Tumor/Blood and Tumor/Muscle (T/M) ratios increased over time, with the T/M ratio reaching a value of almost 5 at 120 min p.i., suggesting a clear differentiation between the affected and nonaffected tissue (Figure 4 & Supplementary Table 1).…”
Section: In Vivo Stability Biodistribution and Imaging Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from the kidneys and blood, no major uptake in all analyzed tissues is noted (<1.5% ID/g from 30 min p.i.). These results are in accordance to ex vivo biodistribution studies previously performed in normal Swiss mice, which showed that 68 GaAGuIX@NODAGA cleared rapidly from the blood via the kidneys to the urine, resulting in extremely low background activity in all other tissues [17]. While the actual tumor uptake dropped from 30 to 120 min p.i., the Tumor/Blood and Tumor/Muscle (T/M) ratios increased over time, with the T/M ratio reaching a value of almost 5 at 120 min p.i., suggesting a clear differentiation between the affected and nonaffected tissue (Figure 4 & Supplementary Table 1).…”
Section: In Vivo Stability Biodistribution and Imaging Studiessupporting
confidence: 91%
“…Previous work from our group has shown that AGuIX derivatives labeled with 68 Ga are a promising imaging tool for simultaneous PET/MRI imaging [17]. The classical AGuIX NPs, made of polysiloxane and surrounded by DOTAGA(Gd 3+ ) covalently grafted to the inorganic matrix, have been modified in order to radiolabele them.…”
mentioning
confidence: 99%
“…Truillet et al [158] synthesized a nanoradiotracer composed by a polysiloxane matrix scaffold surrounded by DOTAGA[Gd 3+ ] and NODAGA[ 68 Ga 3+ ] for PET/MRI. NODAGA and DOTAGA were grafted onto the NP shells by amide bond formation between activated NHS groups of NODAGA and anhydride function of DOTAGA and the amino groups in shell.…”
Section: Other Nanoparticlesmentioning
confidence: 99%
“…Initial work with DOTA as the chelating agent showed promising results, as residual activity on all untargeted tissues was extremely low. The initial encouraging results led Truillet et al (2015) to functionalize these NPs with chelators such as DOTAGA (1,4,7,10-tetraazacyclododecane-1-glutaric anhydride-4,7,10-triacetic acid) [24] and NODAGA (2,2'- [24], [25], for improved radiolabeling. It was demonstrated that a single-injection with 68 Ga-AGuIX@NODAGA nanoparticles could provide a dualmodality imaging agent adequate for both PET and MRI.…”
Section: Gallium-68mentioning
confidence: 99%